1985
DOI: 10.1007/bf02587978
|View full text |Cite
|
Sign up to set email alerts
|

Vergleichende experimentelle Untersuchungen an biologischen Materialien zum Ersatz des vorderen Kreuzbandes

Abstract: Allogeneic and xenogeneic biological tendon and ligament materials for ligament replacement were tested in the knee of rabbits and sheep. In-vitro and ex-vivo biomechanical tests as well as micromorphological investigations following implantation were performed. The preparation procedure mainly consists in cross linking of collagen by dicarboxylic acids (DC). Modifications in the method induce changes in the biomechanical stability also after implantation. Sheep with autologous patellar tendons substitutions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In the interim, prospective studies at different centers have shown no significant difference in the clinical performance between patellar tendon grafts with or without synthetic augmentation (21,23,27). One explanation for this loss of benefit from the ligament augmentation device for autograft procedures could be the different stress-strain relationship of the patellar tendon as compared with the anterior cruciate ligament, since the patellar tendon has been proven to be even stiffer than the ligament augmentation device and thus not stress-protected (1,15,29). On the other hand, the slightly poorer results reported in the literature for other ligament augmentation deviceautograft procedures could be due to the fact that the fixation techniques were different from those used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the interim, prospective studies at different centers have shown no significant difference in the clinical performance between patellar tendon grafts with or without synthetic augmentation (21,23,27). One explanation for this loss of benefit from the ligament augmentation device for autograft procedures could be the different stress-strain relationship of the patellar tendon as compared with the anterior cruciate ligament, since the patellar tendon has been proven to be even stiffer than the ligament augmentation device and thus not stress-protected (1,15,29). On the other hand, the slightly poorer results reported in the literature for other ligament augmentation deviceautograft procedures could be due to the fact that the fixation techniques were different from those used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Various autologous transplantation procedures have been described in the literature, using different tendon grafts (pes anserinus, iliotibial tract, or parts of the patellar tendon) for either augmenting a reattachment or reconstructing the ruptured anterior cruciate ligament. The clinical results have varied (1)(2)(3)6,16,30). To prevent the increasing laxity in the joint (one of the drawbacks after nonaugmented reconstructions of the ruptured anterior cruciate ligament), the synthetic ligament augmentation device (Kennedy model) was introduced (13,19).…”
mentioning
confidence: 99%
“…Clinical studies have been performed by some centres [3,4]. There have been studies on the characteristics of transplantation materials used for substitution of the ACL [1], as well as studies on the mechanical properties of a midsubstance graft taken from the patellar ligament, autologous or homologous [8,9]. Nevertheless, no comparable technical data on the stress-strain relationship and relaxation characterics of synthetic augmentation devices in use were available, quite apart from the question which products of fulfill the requisite criteria for rational use.…”
Section: Discussionmentioning
confidence: 99%